Case report: MRI-negative myelitis following COVID-19 with SEP abnormalities: a case series and literature review - Kawama, Kentaro; Shimazaki, Rui; Sunami, Yoko; Miyakoshi, Natsuki; Tobisawa, Shinsuke; Shimizu, Toshio; Takahashi, Kazushi (Frontiers in Neurology, 2023)
Coronavirus Disease 2019 (COVID-19) is known to have various, neurological manifestations. We herein report three patients with MRI-negative myelitis following COVID-19 with abnormal somatosensory evoked potentials (SEPs). Decreased amplitude of the cortical potential and prolonged latency in the SEPs contributed to diagnosing myelitis in the present patients. The SEP findings improved as the neurological symptoms improved. Despite a delay in initiating immunosuppressive treatment after myelitis onset, all the patients improved clinically. In the light of recent progress in COVID-19 research, several hypotheses can be made to explain the pathophysiology underlying MRI-negative myelitis, including antibody-binding and microglial synapse elimination.